Integrating applied lake ecology into spatial planning: towards a socially acceptable lakeshore restoration at Lake Velence (Hungary) - Boromisza, Zsombor; Ács, Tamás; Pádárné Török, Éva (Acta Geographica Debrecina Landscape & Environment series, 2015)
A good chance of a socially accepted shore-restoration that is sustainable for the long run stands only, if all those, concerned in lake use, are also interested in the ecological interventions, if shore-restoration serves social and economic purposes, as well. In the previous phase of our research, assessments were made to find the sections of the shore zone that are suitable for restoration: to detect the sites where the existing artificial shoreline stabilization works could be removed. So that social demands should be involved in the assessment process, to begin with, structured interviews were made. According to the results, the share of the plots, being suitable or partially suitable for shore-restoration, slightly exceeded 7%. The analysis of restoration’s limiting factors has shown that the type of shoreline stabilization, the width of zone covered by emergent macrophytes, the extent of human pressures, and the relevant regulations on zoning (fixed in urban plans) together set limits to restoration. The interviews have made it clear that as a result of the changed demands on recreation-tourism, also the natural and landscape values have become more significant.